Intestinal Inflammation Induced by Soybean Meal Ingestion Increases Intestinal Permeability and Neutrophil Turnover Independently of Microbiota in Zebrafish - Solis, Camila J.; Hamilton, M. Kristina; Caruffo, Mario; Garcia-Lopez, Juan P.; Navarrete, Paola; Guillemin, Karen; Feijoo, Carmen G. (Frontiers in Immunology, 2020)
Intestinal inflammation is a condition shared by several intestinal chronic diseases, such as Crohn's disease and ulcerative colitis, with severely detrimental consequences in the long run. Current mammalian models have considerably increased understanding of this pathological condition, highlighting the fact that, in most of the cases, it is a highly complex and multifactorial problem and difficult to deal with. Thus, there is an increasingly evident need for alternative animal models that could offer complementary approaches that have not been exploited in rodents, thereby contributing to a different view on the disease. Here, we report the effects of a soybean meal–induced intestinal inflammation model on intestinal integrity and function as well as on neutrophil recruitment and microbiota composition in zebrafish. We find that the induced intestinal inflammation process is accompanied by an increase in epithelial permeability in addition to changes in the mRNA levels of different tight junction proteins. Conversely, there was no evidence of damage of epithelial cells nor an increase in their proliferation. Of note, our results show that this intestinal inflammatory model is induced independently of the presence of microbiota. On the other hand, this inflammatory process affects intestinal physiology by decreasing protein absorption, increasing neutrophil replacement, and altering microbiota composition with a decrease in the diversity of cultivable bacteria.